2015
DOI: 10.1002/cmdc.201500142
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of Ionic Liquids Based on Ampicillin

Abstract: Significant antiproliferative effects against various tumor cell lines were observed with novel ampicillin salts as ionic liquids. The combination of anionic ampicillin with appropriate ammonium, imidazolium, phosphonium, and pyridinium cations yielded active pharmaceutical ingredient ionic liquids (API-ILs) that show potent antiproliferative activities against five different human cancer cell lines: T47D (breast), PC3 (prostate), HepG2 (liver), MG63 (osteosarcoma), and RKO (colon). Some API-ILs showed IC50 va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 21 publications
2
56
0
1
Order By: Relevance
“…There are some doubts in the IL field about the advantages and possibility of using an ion with biological activity for drug application. The important question of the toxicity of ILs has been the main reason behind the delayed entry of these compounds into biological applications . At present, there are some published reports about the development of APIs as ionic liquids and not as crystalline materials …”
Section: Ionic Liquids As Active Pharmaceutical Ingredients (Apis)mentioning
confidence: 99%
See 4 more Smart Citations
“…There are some doubts in the IL field about the advantages and possibility of using an ion with biological activity for drug application. The important question of the toxicity of ILs has been the main reason behind the delayed entry of these compounds into biological applications . At present, there are some published reports about the development of APIs as ionic liquids and not as crystalline materials …”
Section: Ionic Liquids As Active Pharmaceutical Ingredients (Apis)mentioning
confidence: 99%
“…Furthermore, the same ILs showed very low cytotoxicity against two primary cell lines of skin (SF) and gingival fibroblasts (GF), which showed that these compounds are not toxic to human cell lines at the concentration range tested (Table ). This facet of the study is of particular interest, and presents a different point of view from the majority of previously published reports, with the exception of the study reported by Kaushik and co‐workers .…”
Section: Ionic Liquids As Potential Antitumor Agentsmentioning
confidence: 99%
See 3 more Smart Citations